A Minimal Electronic Nose Based on Graphene Functionalized with Metalated Pyrazinoporphyrazines and Phthalocyanines for Ammonia, Benzene, and Hydrogen Sulfide Discrimination - Sonia Freddi; Luca Vaghi; Andrea Penoni; Luca Scapinello; Luigi Sangaletti (Chemosensors)
The development of electronic noses is, nowadays, essential for several applications, including breath analysis and industrial security. Ammonia, benzene, and hydrogen sulfide are particularly important due to their environmental and health impacts. Here, graphene-based sensors, functionalized with unconventional in-house synthesized zinc and copper octyl-pyrazinoporphyrazines and commercially available zinc phthalocyanine, have been prepared. Enhanced solubility given by the octyl chains allowed us to exploit drop-casting as a straightforward functionalization technique. The sensors demonstrated excellent performance for detecting ammonia, benzene, and hydrogen sulfide as a single sensor, with a competitive detection limit and a high sensitivity compared to the state of the art. In particular, functionalization enabled the detection of hydrogen sulfide, for which no response is observed with bare graphene, and lowered the detection limit for all the gases compared to bare graphene. Additionally, the prepared sensors have been assembled into an e-nose that shows promising potentiality to be used for both industrial and medical applications thanks to its excellent discrimination capability of single gases and mixtures.